Proposed Integrated Assessment of RULA, REBA, and OWAS for Ergonomic Risk Evaluation and Workstation Improvement - Purwanto Purwanto; Dzakiyah Widya Ningrum; Muhammad Naufal Hakim; Muhamad Tatmainul Qulub (LPPM Universitas Andalas, 2026)
Manual work with non-ergonomic postures significantly contributes to musculoskeletal disorders (MSDs), affecting worker health and productivity. This study analyzed ergonomic risks at a production workstation using the Rapid Upper Limb Assessment (RULA), Rapid Entire Body Assessment (REBA), and Ovako Working Posture Analysis System (OWAS) methods. A descriptive quantitative approach was applied to seven operators. The results showed that 28.6% of operators were categorized as high risk, 28.6% as moderate risk, and 42.8% as low risk. High-risk postures were associated with upper arm flexion above 60°, trunk bending, non-neutral wrist positions, and manual material handling activities. OWAS analysis identified two operators in action class 3, indicating that corrective actions are needed soon. Ergonomic improvement simulations, including worktable height adjustment, material repositioning, and assistive device use, reduced RULA scores by 40–50%, REBA scores by 35–45%, and OWAS action class from 3 to 2. The study concludes that integrating RULA, REBA, and OWAS provides a comprehensive ergonomic risk assessment and supports effective interventions to reduce MSD risks, improve worker comfort, and enhance productivity.